Relationship of dietary intake between children aged 12–59 months and their mothers in rural Kenya: A cross‐sectional study in two seasons - Kishino, Madoka; Hida, Azumi; Ishikawa-Takata, Kazuko; Tada, Yuki; Kariuki, Lucy; Maundu, Patrick; Matsuda, Hirotaka; Irie, Kenji; Morimoto, Yasuyuki (Wiley, 2024)
Abstract Objective The aim of the study was to investigate the quantitative association between the dietary intakes of children and their caregivers. Method In this cross‐sectional study, a non‐consecutive 2‐day 24‐h dietary recall was conducted in two seasons. Participants comprised 142 pairs of 12–59‐month‐old children and their female caregivers from rural areas of Kenya. Energy and micronutrient adequacy, food group intakes and food allocation were assessed. Differences and correlations between caregiver and child diets were examined, and multiple regression analysis was used to investigate the relationship between the children's and caregivers’ dietary intakes. Results The child's diet was significantly lower in energy and higher in micronutrient adequacy than was the caregiver's diet ( p < 0.001). Specifically, the child's diet contained more fruits, dairy products, sugar and confectionaries per 4184 kj. Children were allocated relatively more dishes containing nutrient‐rich foods than staple foods. The correlation coefficients between the dietary intake of caregivers and children were stronger among 24–59‐month‐old children. After controlling with covariates, caregiver energy intake was significantly associated with child energy intake (standardised beta [ β ] = 0.512, p < 0.001), and caregiver micronutrient adequacy was associated with child micronutrient adequacy ( β = 0.679 and β = 0.262 after energy adjustment, p < 0.001). Conclusions The dietary intakes of caregivers and children were closely related. The children had a more nutrient‐rich diet compared to that of their caregivers. Differences in food group intakes and food allocation may contribute to the higher nutrient adequacy of children. There is a need to improve the diet of caregivers, which would contribute to improving the diet of children.